TribUTE-F assay: Fluorescence-based rapid quantification of dietary intake in the red flour beetle, Tribolium castaneum (Coleoptera: Tenebrionidae), facilitates evaluation of antifeedant inhibitory effects. (June 2018) - Kikuta, Shingo
Abstract: Tribolium castaneum (Herbst.) is an important pest of stored grains, nuts, and cereals worldwide. Different methods have been used to estimate dietary intake and feeding preferences of this beetle. A previously described TribUTE ( Trib olium U rgesT oE at) assay estimates its dietary intake by measuring the amount of gypsum excreta in beetles fed gypsum, a non-digestible and non-toxic compound, using an analytical microbalance. The method revealed the sweet preferences of T . castaneum adults. However, the measurements based on microbalance require individual quantitation of each sample, and the weight of the samples is sometimes below the detection limit of the microbalance. Here, an improved TribUTE assay, designated TribUTE-F assay, that uses gypsum labeled with the fluorescence dye ROX as an endogenous tracer is described. The fluorescence intensity remains constant during the consumption and excretion of the labeled gypsum and it is strongly correlated with the amount of gypsum. This approach was then used to evaluate the inhibitory effect of an antifeedant, mulberry latex, on dietary intake of T . castaneum adults. Compared with microbalance measurements, the new method enables more accurate measurement of near the minimum detectable quantities and is a suitable tool for the discovery of antifeedants. Graphical abstract: Highlights: TribUTE-F assay measures the amount of gypsum excreta in beetles. Compared with microbalance measurements, the assay is more accurate and less time-consuming. It was used to evaluate the inhibitory effect of antifeedant on dietary intake of Tribolium castaneum.